Parasitological and clinical correlates of Plasmodium–Schistosoma mansoni co-infection and its determinants among Plasmodium-infected patients in the Wolaita Zone, South Ethiopia regional state - Mohamed, Kemal; Belay, Tariku; Zeynudin, Ahmed (Frontiers in Malaria, 2025)
BackgroundMalaria and schistosomiasis are among the most important parasitic diseases with overlapping geographical distribution in Ethiopia. The objective of this study, therefore, was to assess parasitological and clinical correlates and determinants of co-infection among malaria patients.MethodsA health facility-based comparative cross-sectional study was conducted among malaria patients attending public health facilities in Damot Woyide district, Wolaita zone, South Ethiopia regional state, from December 2020 to June 2021. A total of 246 (123 Plasmodium-only and 123 Plasmodium–Schistosoma mansoni co-infected) study participants were sampled consecutively. A pre-tested structured questionnaire was used to collect data on demographic and risk factors. Detection and quantification of Schistosoma mansoni ova and malaria parasites were done with the Kato–Katz technique and blood film, respectively. Determination of hematological and biochemical parameters was done by the aLCose®HemoGo test system and the Cobas C 311 chemistry analyzer, respectively.ResultsThe prevalence of Plasmodium–Schistosoma mansoni co-infection was 18.2%. Plasmodium–Schistosoma mansoni co-infected with a heavy intensity of Schistosoma mansoni had the highest parasitemia and was also significantly associated with malaria attack. In addition, anemia was associated with the presence of Plasmodium–Schistosoma mansoni co-infection. Schistosoma mansoni co-infection among malaria patients significantly increased mean Plasmodium density, serum glutamate oxaloacetate transaminase, serum glutamate pyruvate transaminase, alkaline phosphatase, direct bilirubin, and total protein. Hemoglobin and hematocrit were significantly lower among co-infected individuals. On multivariate analysis, being male (AOR=3.03, CI: 1.56-5.91,p=0.001), being in the 6-15 years age group (AOR = 5.85, CI: 2.45–13.93,p=0.00), the presence of stream (AOR = 4.1, CI: 1.65–10.15,p=0.002), having a water body distance of less than 1,000 m (AOR=2.33, CI: 1.23–4.41,p=0.009), and presence of irrigation practice (AOR= 3.24, CI: 1.69–6.18,p=0.00) were found to be significant risk factors of co-infection.ConclusionMalaria attack and level of parasitemia were associated with the intensity of concurrent Schistosoma mansoni infection. Co-infection results in the change of Plasmodium density, hematological, and biochemical parameters in malaria patients.